Artificial Intelligence in Pediatric Dentistry (Academia Journal of Medicine, 2024)
Artificial intelligence (AI) has gained significant momentum in the field of pediatric dentistry, with applications aimed at improving diagnostics, treatment planning, patient engagement, and research. The integration of AI technologies in dental practices offers potential to enhance the accuracy of diagnoses, predict treatment outcomes, customize patient-specific treatments, and streamline practice management. AI-driven tools, such as machine learning algorithms, can analyze complex dental data, including radiographs, photographs, and clinical notes, to aid in early detection and management of oral diseases prevalent in children. Moreover, AI can provide educational resources tailored to young patients, fostering better oral health habits.
Keywords: Artificial intelligence; Pediatric Dentistry; Applications